A method for source-microphone range estimation in reverberant environments, using an array of microphones of unknown relative position - BOLAND, FRANCIS MORGAN (IEEE, 2006)
Estimating the range between an acoustic source and a microphone is a central problem in microphone-array processing. Although many approaches have been proposed in the literature, these tend to require knowledge of the relative microphone positions. We propose a range estimation method, for use in reverberant environments and where the relative positioning of the elements of a microphone-array is unknown. We demonstrate the effectiveness of this method under real, reverberant conditions.
ISSC 2006
PUBLISHED
Keywords: Range estimation; Microphone arrays